Ethnic Bullying Victimization in Italy: The Role of Acculturation Orientation for Ethnic Minority Adolescents With Differing Citizenship Statuses - Palladino, Benedetta Emanuela; Nappa, Maria Rosaria; Zambuto, Valentina; Menesini, Ersilia (Frontiers in Psychology, 2020)
This study examines the role of acculturation orientation towards home and host countries in ethnic bullying victimization, by considering citizenship status and taking into account social withdrawal. Within a larger school project with middle and high school students, we analyzed data on 252 adolescents from immigrant backgrounds: 71 born abroad without Italian citizenship (Males=71.4%; mean age=13.98, SD=1.7); 96 born in Italy to immigrant parents and without Italian citizenship (Males=58.3%; mean age=13.26, SD=1.6); and 85 Italian citizens born in Italy with an immigrant parent (Males=54.7%; mean age=13.12, SD=1.5). At the univariate level we found that the group of adolescents born abroad with foreign parents showed significantly higher levels of ethnic victimization compared to the group of adolescents born in Italy with an Italian parent. The latter also reported a significantly higher mean in Acculturation Orientation toward their Host Country (i.e. Italy) compared to the other two groups. Looking at the processes working within each group, we found differences in the patterns of association between acculturation orientation and ethnic bullying victimization. Specifically, we found a significant and positive association between acculturation orientation toward the home country and ethnic victimization in the two groups of adolescents born in Italy, while acculturation orientation toward the host country seems to be a protective factor only for adolescents with Italian citizenship. Acculturation orientation does not play any role in ethnic victimization for the first generation of immigrants, while for this group we found a stronger positive effect of Social Withdrawal. Citizenship status appears to be a good indicator of belonging to an ethnic minority group with a background of immigration: it seems to catch specific processes in ethnic bullying victimization.